"Falling through the cracks." A case analysis of financial elder abuse and neglect using coronial evidence. Issue 5 (20th October 2022) - Lawrence, Suanne; Henning, Terese; Banks, Susan; Bartkowiak-Théron, Isabelle
ABSTRACT: The Preventing Elder Abuse Tasmania (PEAT) research group was asked by the State Coroner to review and report on findings from the inquest into the death of a 77-year-old woman (MM) which forms the basis of this analysis. MM died of hypothermia while sleeping in a converted shipping container at her daughter and son-in-law's southern Tasmanian property. Five years later this couple were convicted of MM's manslaughter. At the subsequent inquest in 2017–2018 the public heard that MM was in the advanced stages of dementia, as well as frail and underweight at the time she died. Whereas it was significant physical neglect by her family that ultimately caused her death, the seven years of abuse to which she was subjected started with fraud, supported by a lack of legislative protections.